Pengembangan Model Discovery Learning dalam Pembelajaran Bahasa Indonesia SD/MI - Dyah Afifah Andari (LP2M, Institut Agama Islam Qamarul Huda, 2024)
Indonesian language learning is a challenge at SDN Turi 1 Blitar, because in the lower grades many are still unable to read, make conclusions and answer questions. So it must be carried out with teacher guidance. In learning Indonesian, teachers only use lecture and discussion methods so that students are more easily bored and passive. One of the efforts that can be applied is using the discovery learning model in Indonesian language learning to foster students' reading and writing skills. The purpose of this research was to analyze the planning and implementation of the discovery learning model in Indonesian language learning in the low grades of SDN Turi 1 Blitar. This research uses a qualitative approach with a case research type. Case research is a type of qualitative approach that examines a particular case in the context of real life. The data used were primary and secondary data. The data were collected through three ways, interviews, observation, and documentation. The results of this research show that planning is done by considering the characteristics of students, class conditions, determining learning objectives, designing lesson plans in accordance with the syllabus and student books adapted to the stages of the discovery learning model. Implementation in the discovery learning model includes, providing stimulation, identifying problems, collecting data, processing data, proving, and conclusions. The assessment was carried out by class observation, and worksheets of low-grade students of SDN Turi 1 Blitar. As a result, students showed the ability to convey ideas, independently read, do tasks, write new vocabulary and arrange vocabulary into simple sentences individually.